Evolving Otolaryngology Resident Roles and Concerns at the Peak of the US COVID‐19 Pandemic. Issue 12 (14th September 2020) - Cai, Yi; Gulati, Arushi; Jiam, Nicole T.; Wai, Katherine C.; Shuman, Elizabeth A.; Pletcher, Steven D.; Durr, Megan L.; Chang, Jolie L.
Abstract: Background: The roles of US otolaryngology residents have changed in response to the coronavirus disease 2019 (COVID‐19) pandemic. As the pandemic peaked in the United States, we characterized resident activities and concerns. Methods: A cross‐sectional study of US otolaryngology residents between April 20, 2020 and May 2, 2020. Results: A total of 219 residents at 65/118 (55%) institutions responded. Thirty (14%) residents had been redeployed. Residents reported greatest concerns regarding education ( P  < .00001). Assuming adequate protective equipment, 55% desired active participation in high‐risk procedures on COVID‐19‐positive patients. Redeployed residents had greater concern for burnout and reduced in‐hospital well‐being ( P  < .05). Resident satisfaction correlated with comfort communicating concerns to their department (odds ratio [OR] = 4.9, 95% confidence interval [CI] 1.4‐17.3, P = .01) and inversely correlated with low perceived meaning in work (OR = 3.1, CI 1.1‐9.1, P = .03). Conclusion: Otolaryngology resident concerns have evolved as the pandemic progressed. Residency programs should prioritize resident education, well‐being in redeployed residents, and open communication as they transition toward recovery.